Structural, elastic, and, strain induced electronic and magnetic properties of half-Heusler alloys MnSnX (X = Ni, Cu, and Pd) (BIBECHANA, 2026)
Half-metallic (HM) ferromagnetic materials have garnered significant attention due to theirpotential applications in solid-state electronic devices. Strain manipulation offers a promisingavenue for tuning the physical properties of such materials. In this regard, the structural, elas-tic, and strain effect on electronic and magnetic properties of half-HeuslerMnSnX (X = Ni,Cu, and Pd) alloys have been studied in this work. Our findings revealed that these compoundsexhibit negative formation and cohesive energies, indicative of their chemical stability and po-tential for experimental synthesis, with the exception of MnSnCu. Elastic property analysisfurther demonstrated the mechanical stability of all compounds, yet their inherent brittleness.We observed HM behaviour under uniform compressive strain ranging from -5% to -14% inMnSnNi and MnSnPd, with band gaps between 0.499 and 0.822 eV calculated using the GGAmethod whereas MnSnCu does not exhibit HM character. This is a noteworthy departure fromthe unstrained system (0%). The mBJ method further validated HM characteristics, exceptfor MnSnCu under compressive strain thresholds of ≤ −6% and ≤ −12% for MnSnNi andMnSnPd, respectively. The magnetic properties under uniform compressive strains, whereHM nature is achieved, conform to the Slater-Pauling 18-electron rule, boasting 100% spinpolarization near the Fermi level. This polarization primarily stems from the transition metalMn, with minor contributions from Ni, Pd, and Sn. In light of our findings, we proposethat the electronic and magnetic attributes of these materials can be enhanced through theapplication of strains, potentially making them attractive for spintronic applications.